Deployment of dentists in COVID-19 case investigation and contact tracing: An example from Turkey - Ozkan, Ozlem; Sevim, Neslihan; Ocek, Zeliha (German Medical Science GMS Publishing House, 2023)
Aim: In Turkey, dentists working in public dental care centers were deployed in COVID-19 case investigation and contact tracing (CICT) teams during the pandemic. This study aims to explore the experiences of the dentists assigned to teams undertaking COVID-19 CICT practices to determine how healthcare workers should be supported when working in pandemic response and other crises. Material and method: The sample of this qualitative, phenomenological study consisted of thirty four public dentists assigned to COVID-19 CICT practices in four metropolitan areas of Turkey. Data were collected through semi-structured in-depth interviews that were conducted online in August and September 2020. The data were analyzed using thematic content analysis. Results: Six themes were revealed: preparation for CICT, basic requirements, work relations, working conditions, being a dentist assigned to CICT and COVID-19 pandemic management. The dentists complained that they were not appropriately assigned to CICT, as they lacked the preparations and sufficient training. They had to acquire personal protective equipment and other basic needs at their own expense. The working conditions were severe, and they had negative relations at work. The State and the Ministry of Health were criticized for inadequate implementation of institutional measures for COVID-19 pandemic management. Conclusions: The study showed that dentists were motivated to participate in the management of pandemics and similar crisis situations, but in a negative work environment - where they were deployed without adequate training, preparation, and ensuring their basic needs and requirements were met - they lost this motivation, and experienced stress and feelings of inadequacy.